Medical image understanding and analysis: 27th annual conference, MIUA 2023, Aberdeen, UK, July 19-21, 2023 : proceedings - Waiter, Gordon; Lambrou, Tryphon; Leontidis, Georgios; Oren, Nir; Morris, Teresa; Gordon, Sharon (Lecture notes in computer science, 2024)
This book constitutes the proceedings of the 27th Annual Conference on Medical Image Understanding and Analysis, MIUA 2023, which took place in Aberdeen, UK, during July 19-21, 2023.The 24 full papers presented in this book were carefully reviewed and selected from 42 submissions. They were organized in topical sections as follows: Image interpretation; radiomics, predictive models and quantitative imaging; image classification; and biomarker detection